Recommendations for ammonia borane composite pellets as a hydrogen storage medium - Keskin, Elif; Filiz, Bilge Cosukuner; Depren, Serpil Killc; Figen, Aysel Kanturk (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
The perspective of this study describes a new concept for ammonia borane (NH3BH3, AB) in the form of pellet composited with Co-B catalyst to use as a hydrogen storage medium. For the purpose of this, hydrogen storage capacity and physical-chemical properties of composite pellet are examined and tested to investigate effects of specified environmental conditions by exposing pellets in temperature from 22 degrees C to 80 degrees C in a long period of time (1 day-4 months). A statistical strategy is provided to detail the investigation for significant differences between holding conditions and their interactions. These results suggest that the changing in holding time is more important than the temperature. The general point of view, there is no change in hydrogen storage properties when the composite pellets held at low temperature about 22 degrees C for 3 months, and the same trend is also preserved when the composites are kept at the higher temperature for a week. It is concluded that the composite pellets shown performance at hydrogen storage with easy handling and controlled hydrogen generation for on-board energy applications. (C) 2018 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Ammonia borane; Hydrogen; Storage; Pellet; Composite; Hydrolysis; ENHANCED KINETICS PERFORMANCE; HYDROLYTIC DEHYDROGENATION; THERMAL-DECOMPOSITION; ENERGY EFFICIENCY; MG3RE HYDRIDES; CO-B; GENERATION; CATALYSTS; NI; NANOPARTICLES; Chemistry; Electrochemistry; Energy & Fuels